Compare features of human dental pulp cells cultured from pulp tissues with and without cryopreservation - Yan, Ming; Nada, Ola A.; Smeets, Ralf; Gosau, Martin; Friedrich, Reinhard E.; Kluwe, Lan (Biomedical papers, 2021)
Background and Aims. Teeth extracted are usually disposed as bio-waste whereas they could serve as an autologous tissue for culturing multipotent dental pulp cells which have application potential in regenerative medicine. This study aimed to examine the feasibility of cryopreserving dental pulp tissue at teeth extraction for later culturing of cells. Methods. The pulp tissue from each of a total of 10 teeth was cut into small fragments which were then divided into two portions. One portion was directly used for culturing pulp cells using the explant method. The other portion was cryopreserved with 10% DMSO in liquid nitrogen for at least one month and then thawed for culturing pulp cells. Results. Vital cells were obtained from all the 10 pulp fragment suspensions which went through cryopreservation. The cell outgrowth from the explants of cryopreserved pulp fragments was two days later than that of corresponding fresh pulp tissue. Otherwise, no difference was observed in proliferation, expression of stem cell markers and differentiation into adipose cells and osteoblasts between the two groups of cells cultured from the fresh or the cryopreserved pulp fragments. Conclusions. Cryopreserving fragmented dental pulp tissue provides a feasible option for saving pulp tissues as autologous cell sources for possible later application.
Keywords: dental pulp cells; differentiation; dental pulp tissue; cell culture; tissue cryopreservation; osteogenic differentiation; adipogenic differentiation